Mechanisms underlying CO2 retention during flow-resistive loading in patients with chronic obstructive pulmonary disease. - Oliven, A (1983)
The present study examined the respiratory responses involved in the maintenance of eucapnea during acute airway obstruction in 12 patients with chronic obstructive disease (COPD) and 3 age-matched normal subjects. Acute airway obstruction was produced by application of external flow-resistive loads (2.5 to 30 cm H2O/liter per s) throughout inspiration and expiration while subjects breathed 100% O2. Application of loads of increasing severity caused progressive increases in PCO2 in the patients, but the magnitude of the increase in PCO2 varied substantially between subjects. On a resistance of 10 cm H2O/liter per s, the highest load that could be tolerated by all COPD patients, the increase in PCO2 ranged from 1 to 11 mm Hg, while none of the normal subjects retained CO2. Based on the magnitude of the increase in PCO2 the patients could be divided into two groups: seven subjects whose PCO2 increased by less than or equal to 3 mm Hg (group I) and five subjects whose PCO2 increased by greater than 6 mm Hg (group II). Base-line ventilation and the pattern of breathing were similar in the two groups. During loading group I subjects maintained or increased tidal volume while all group II patients decreased tidal volume (VT). The smaller tidal volume in group II subjects was mainly the result of their shorter inspiratory time as the changes in mean inspiratory flow were similar in the two groups. The magnitude of CO2 retention during loading was inversely related to the magnitude of the change in VT (r = -0.91) and inspiratory time (Ti) (r = -0.87) but only weakly related to the change in ventilation (r = -0.53). The changes in PCO2, VT, and Ti during loading correlated with the subjects' maximum static inspiratory pressure, which was significantly lower in group II as compared with group I patients. These results indicate that the tidal volume and respiratory timing responses to flow loads are impaired in some patients with COPD. This impairment, presumably due to poor inspiratory muscle function, appears to lead to CO2 retention during loaded breathing.